The Effect of Fraud Pentagon on Earnings Management with Audit Committee as Moderating Variable - Cahyani, Rossy Angga Mustika; Ardini, Lilis; Kurnia, Kurnia (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
his study aimed to examine the effect of fraud pentagon, external pressure, financial targets, ineffective monitoring, change in auditor, change of directors, and a frequent number of CEO’s pictures on earnings management; with the audit committee as moderating variable. The population was State-Owned Enterprises that were listed on Indonesia Stock Exchange (IDX) during 2015-2019. The Sampling technique used purposive sampling with 12 State-Owned Enterprises as the sample. Furthermore, there were 2 models of analysis, i.e. multiple linear regression and Moderated Regression Analysis (MRA) in order to analyze the secondary data in form of companies’ financial statements; . As a result, it concluded that external pressure, financial target, and a frequent number of CEO’s pictures affected earnings management. However, ineffective monitoring, change in auditor, and change of directors did not affect earnings management. In contrast, the audit committee was able to moderate the effect of external pressure, financial targets, change of director, and a frequent number of CEO’s pictures on earnings management. On the other hand, the audit committee was not able to moderate the effect of ineffective monitoring and change in auditor on earnings management.